IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SATUAN PAUD - Femiaulia Riza; Taqwa, Rahmi; Hadiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Implementation of multicultural education in PAUD units has an important role in instilling the values ​​of diversity, tolerance and respect for differences from an early age. Multicultural education aims to form an early generation capable of living side by side in harmony. This research aims to provide an understanding for educators about how to implement multicultural education in PAUD units to increase effectiveness in an exciting learning process. Researchers used a qualitative approach with literature studies adapted to the topic of discussion. This research provides practical recommendations for educators to create an inclusive learning environment that supports the realization of multicultural education from an early age. Keywords: Multicultural education, early childhood, Implementation